Racial/Ethnic Transition and Hierarchy Among Ascending Neighborhoods. Issue 6 (November 2019) - Owens, Ann; Candipan, Jennifer
This article examines the racial/ethnic population dynamics of ascending neighborhoods—those experiencing socioeconomic growth. Drawing on Census and American Community Survey data from 1990 to 2010, we first explore whether changes in racial/ethnic composition occur alongside ascent. We find that, while most neighborhoods' racial/ethnic composition does not dramatically change during this period, neighborhoods that experienced ascent are much more likely to transition from majority-minority to mixed race or predominantly White than nonascending neighborhoods. Then, we use microdata to analyze whether two potential drivers of ascent, the in-migration of higher-socioeconomic status (SES) households and changes in the fortunes of long-term residents, are racially/ethnically stratified. We argue that the process of neighborhood socioeconomic ascent perpetuates neighborhood racial/ethnic hierarchy. While most Black and Hispanic neighborhoods remain majority-minority, those that ascend are more likely to experience a succession of high-SES White residents replacing minority residents.